PENGARUH KECERDASAN EMOSIONAL, IKLIM KERJA DAN KOMPETENSI TERHADAP KINERJA GURU DI SMA NEGERI 6 BINJAI KECAMATAN BINJAI UTARA - Evi Aryanti (Manajemen dan Bisnis, 2020)
The formulation of the problem in this study is How the influence of Emotional Intelligence, Work Climate and Competence on Teacher Performance in SMA Negeri 6 Binjai, North Binjai District, both partially and simultaneously. The population and sample of this study were all teachers in the school, amounting to 64 people. The sampling technique uses total sampling. Data collection techniques used were direct interviews and questionnaires. The results of this study are partially the Emotional Intelligence variable has a positive and significant effect on Teacher Performance with tcount ttable, (2.633 2.00,), Work Climate variable has a positive and significant effect on Teacher Performance with tcount ttable, (2,812 2.00) and Competency Variables have a positive and significant effect on Teacher Performance with tcount ttable, (2.701 2.00). Simultaneously the variables of Emotional Intelligence, Work Climate and Competence have a positive and significant effect on Teacher Performance with Fcount Ftable, (11,492 2.75). R2 (RSquare) value of 0.625, which means that the variable Emotional Intelligence, Work Climate and Competence has a positive and significant effect on Teacher Performance in SMA Negeri 6 Binjai, North Binjai district, 62.50%, and the remaining 37.50%, influenced by other factors not examined.